2017
DOI: 10.3945/ajcn.116.143453
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of α-linolenic acid and risk of age-related macular degeneration ,

Abstract: Background:The relation between a-linolenic acid (ALA), a plant-derived omega-3 (n-3) fatty acid, and age-related macular degeneration (AMD) is unclear. European researchers reported that #40% of ALA can be present as trans forms. Objective: We aimed to evaluate the associations between intake of ALA and intermediate and advanced AMD. Design: Seventy-five thousand eight hundred eighty-nine women from the Nurses' Health Study and 38,961 men from Health Professionals Follow-Up Study were followed up from 1984 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Table shows an overview of different kinds of systemic lipid factors and their association with the development of early and late AMD, as identified in prospective cohort studies. Of note, most prospective studies investigating fatty acids have estimated the systemic levels based on food frequency questionnaires and only a minority of the studies have measured systemic blood levels …”
Section: Molecular Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table shows an overview of different kinds of systemic lipid factors and their association with the development of early and late AMD, as identified in prospective cohort studies. Of note, most prospective studies investigating fatty acids have estimated the systemic levels based on food frequency questionnaires and only a minority of the studies have measured systemic blood levels …”
Section: Molecular Risk Factorsmentioning
confidence: 99%
“…Whether increased dietary intake or higher systemic levels of ALA are associated AMD progression is not clear. Three longitudinal population studies showed no association between a higher dietary intake of ALA and AMD progression, and three prospective studies on systemic ALA levels reported conflicting results: one study showed that higher plasma ALA levels were associated with a decreased risk of developing GA and nAMD, while two other studies showed an increased risk of developing early and late AMD …”
Section: Molecular Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical trials have focused on the prevention of AMD progression, and the data from Age-Related Eye Disease Study 2 (AREDS2) showed that AREDS formulation in primary analyses did not further reduce the risk of progression to advanced AMD 19. Additionally, several epidemiological studies and meta-analyses demonstrated that omega-3 fatty intake was associated with a lower risk of AMD; however, the conclusion should be validated by more well-designed clinical studies 20,21. Clinical application of nutrition supplementation for the treatment of early AMD is still far from being a reality.…”
Section: Introductionmentioning
confidence: 99%